Screening of Phytochemical and Antibacterial Property of Some Local Herbs of Meghalaya - Sanjukta, R.K.; Das, S.; Puro, K.; Ghatak, S.; Shakuntala, I.; Sen, A. (Indian Journal of Hill Farming, 2019)
The present study was conducted to evaluate the antibacterial properties of four plant species, selected on the basis of folklore medicinal reports practiced by the tribal people of Meghalaya. In-vitro antibacterial properties of alcoholic (Ethanolic and methanolic) and aqueous extracts of leaves of four plant species, were assayed against four bacteria viz. Gram positive (Staphylococcus aureuss and Listeria monocytogenes) and Gram negative (Escherichia coli and Salmonella Typhimurium) using both agar well diffusion and disc diffusion method. All four plants viz. Centella asiatica, Eupatorium cannabium, Galinsoga parviflora and Clerodendrum serratum showed control of growth. The maximum inhibitions were observed in Galinsoga parviflora against Staphylococcus and Listeria monocytogenes, followed by. Clerodendrum serratum, Centella asiatica and Eupatorium cannabium. The different extracts differed significantly in their antibacterial properties with the methanolic extract being more effective followed by ethanolic extract. Aqueous extract showed very least activity. The results highlight that some of the studied plants had good antibacterial properties.